Clinicopathological and immunological profiles of prostate adenocarcinoma and neuroendocrine prostate cancer - Gang Huang; Huaru Zhang; Haoqing Shi; Wenhui Zhang; Tao Wang; Ziwei Wang; Qing Chen; Bijun Lian; Jing Li; Guosheng Yang (World Journal of Surgical Oncology, 2022)
Abstract Background Biomarkers of DNA damage repair deficiency provide opportunities for personalized treatment with immunotherapy. However, there is limited research on the immune microenvironment of adeno-neuroendocrine prostate cancer (NEPC). In this study, we aimed to assess and describe the comprehensive clinicopathological manifestations of NEPC to improve diagnosis and predict prognosis. Methods A retrospective medical record review of 66 patients with prostate cancer (PCa) was performed. PCa samples from the 66 patients were analyzed using immunohistochemical staining for the detection of chromogranin, neural cell adhesion molecule 1, and synaptophysin. For tumor-associated immune microenvironment analysis, PD-L1, CD3, and CD8 were labeled in tissue slides. The effect of clinicopathological factors on the survival of patients with Adeno-NEPC was analyzed. Results Twenty patients presented with adeno-NEPC, whereas 46 presented with adeno-PCa. The median age of patients at PCa diagnosis was 67.86 ± 7.05 years (68.65 ± 7.23 years, adeno-NEPC; 67.52 ± 7.02 years, adeno-PCa). Eleven patients with adeno-NEPC underwent prostatectomy, whereas nine received primary androgen deprivation therapy (ADT). Additionally, 30 patients with adeno-PCa underwent prostatectomy, whereas 16 (34.8%) received primary ADT. There was a significant difference in overall survival between patients with adeno-NEPC and those with adeno-PCa (46.0 months vs. 65.0 months). There was also a significant difference in time from prostatectomy to biochemical recurrence between the groups of patients who underwent prostatectomy. Prostatectomy and normal lactate dehydrogenase levels were clinical factors that were significantly associated with better outcomes in patients with adeno-NEPC. Metastatic adeno-NEPC was associated with a higher programmed death ligand 1 (PD-L1) score (2–4) than localized PCa. The data showed that PD-L1 expression in adeno-NEPC may be negatively associated with that in CD8+ T cells. Conclusions Our study revealed clinicopathological manifestations of adeno-NEPC and some possible predictive factors significantly associated with better outcomes in patients with adeno-NEPC. These findings might be beneficial in the development of diagnostic strategies and customized treatment plans.